The Influence of Bank Health Level Using RGEC on Financial Distress of Banks in Indonesia - Ainun Djariyah; Susi Retna Cahyaningtyas; Zuhrotul Isnaini (Postgraduate, University of Mataram, 2023)
This study aims to analyze the effect of the soundness level of RGEC-based banks on financial distress banks listed on the IDX in 2018-2021. The number of samples used were 43 banking companies, with the saturated sample method. This research is a causal associative research with a quantitative approach and using logistic regression analysis techniques. Risk profile is measured by NPL/NPF and LDR/FDR, GCG variable is measured by self-assessment GCG, variable earning measured by ROA, NIM, and BOPO, as well as variables capital measure with CAR. The results showed that NPL, ROA, NIM, and BOPO had no effect on financial distress, while LDR, GCG, and CAR have an effect on financial distress banking company. This research contains implications so that in the future the parties related to the condition financial distress pay more attention to the ratios that affect financial distress and maintain the ratio to remain in good condition.